Políticas de atenção à saúde e segurança do servidor (PASS) e os efeitos na atuação do tradutor intérprete de Libras - Mendes, Grace Kelly (2022)
This dissertation presented to the Graduate Program in Education (PPGE) of the Federal University of Santa Maria (UFSM), linked to Research Line 3 (LP3) - Special Education, Inclusion and Difference, has the general objective: To analyze the impacts of Health Care and Safety Policies of the Federal Public Servant (PASS), in the performance of the Libras/Portuguese Interpreter Translator (TILSP), in the federal universities of Rio Grande do Sul. Specifically, the aim is to: a) present the public policies of attention to health and safety at work for federal public servants; b) investigate whether the Tilsp have knowledge about the public policies that support the health and safety of the server; c) identify the category's claims about Tilsp's health care; d) verify the practices of self-care with the physical and mental health of the Tilsp; e) discuss the position of the Tilsp regarding adherence to the projects provided by the institution in return for the current policies offered. The study assumes an exploratory character, of a qualitative nature, of the bibliographical type. Structured interviews were carried out with interpreters from the federal universities of Rio Grande do Sul and the answers to the questionnaires that were applied online were analyzed, using open, closed and multiple-choice questions, through content analysis. In general, Tilsp are susceptible to musculoskeletal disorders due to current work conditions and demands. We found groups with repetitive strain injuries (RSI) such as carpal tunnel syndrome. These injuries can be caused by several reasons, among them we have work overload both due to the workload and the lack of rotation, the lack of ergonomic resources, as well as not having prior knowledge of the content to be interpreted. These factors can cause these professionals to leave their work, generating an overload of work for the other interpreters on the team. The base documents of the policy do not explicitly present interventions. Emphasizing the importance of having a single policy document, which makes it fragmented. It is necessary for Tilsp to know the risk factors in the profession and the importance of prevention, as this is perhaps one of the main causes for injuries not to be triggered. In addition, referrals to preventive physiotherapy programs on ergonomic issues within institutions may become recurrent. Servers find it difficult to dedicate themselves to health care, most of the reasons include lack of time, lack of service, incompatibility of schedules and motivation. The results found demonstrate that the policy actions should not be implemented in isolation, understanding that the quality of life at work comes from a set of perceived needs in the institution.